2022
DOI: 10.1021/jacs.2c09056
|View full text |Cite
|
Sign up to set email alerts
|

Stabilized Nitrogen Framework Anions in the Ga–N System

Abstract: Nitrogen-rich compounds have attracted significant fundamental and practical interest owing to their ability to accommodate diverse nitrogen-bonding patterns and their feasibility as high-energy-density materials. Herein, we examine a wide range of chemical compositions in the compressed Ga–N system using first-principles structural search and experimental preparation using a laser-heated diamond anvil cell. Our investigations have theoretically identified three thermodynamically stable stoichiometriesGaN15, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 72 publications
1
8
0
Order By: Relevance
“…The sample collected after pure 14 N 2 treatment showed a main signal centered at 1447 cm – 1 . After the 15 N 2 treatment, the signal was split into two peaks at 1397 and 1418 cm –1 , which agreed well with the isotopic effect induced by the change of 14 N 2 to 15 N 2 and 15 N 14 N. These signals can be attributed to stretching vibrations of (N 2 ) 2 – anions, so-called diazenide, as identified in high-pressure stabilized inorganic materials and organic complexes. , Moreover, the Raman signal for (N 2 ) 2 – anions almost disappeared when Ba 2 N was further heated in He at 600 °C (Figure S18). Therefore, N 2 desorption in the low-temperature range (290–570 °C) is confirmed to result from the release of (N 2 ) 2 – anions that are formed as intermediates of N 2 dissociation on/in Ba 2 N.…”
supporting
confidence: 67%
“…The sample collected after pure 14 N 2 treatment showed a main signal centered at 1447 cm – 1 . After the 15 N 2 treatment, the signal was split into two peaks at 1397 and 1418 cm –1 , which agreed well with the isotopic effect induced by the change of 14 N 2 to 15 N 2 and 15 N 14 N. These signals can be attributed to stretching vibrations of (N 2 ) 2 – anions, so-called diazenide, as identified in high-pressure stabilized inorganic materials and organic complexes. , Moreover, the Raman signal for (N 2 ) 2 – anions almost disappeared when Ba 2 N was further heated in He at 600 °C (Figure S18). Therefore, N 2 desorption in the low-temperature range (290–570 °C) is confirmed to result from the release of (N 2 ) 2 – anions that are formed as intermediates of N 2 dissociation on/in Ba 2 N.…”
supporting
confidence: 67%
“…34−36 Among them, the P4/nmm-BeN 4 , γ-BeN 4 , δ-BeN 4 , WN 6 , MN 10 , and MN 15 compounds are recoverable at ambient pressure. Experimentally, LiN 5 and CsN 5 with N 5 rings, 37,38 K 2 N 6 with N 6 ring, 39 MgN 4 , Mg 2 N 4 , and tr-BeN 4 with armchair chains, 40−42 and layered GaN 5 43 have been synthesized at 45−85 GPa. Furthermore, LiN 5 , tr-BeN 4 , and Mg 2 N 4 can be quenched to ambient conditions.…”
Section: Introductionmentioning
confidence: 99%
“…For instances, P 4/ nmm -BeN 4 with N 4 ring, MN 10 (M = Be, Mg, and Zn), and MN 15 (M = Al, Ga, Sc, and Y) compounds with N 5 rings, R 3̅ m -WN 6 with N 6 ring, γ-BeN 4 and δ-BeN 4 with armchair chains, and layered BeN 4 , GaN 5 , and ScN 5 . Among them, the P 4/ nmm -BeN 4 , γ -BeN 4 , δ -BeN 4 , WN 6 , MN 10 , and MN 15 compounds are recoverable at ambient pressure. Experimentally, LiN 5 and CsN 5 with N 5 rings, , K 2 N 6 with N 6 ring, MgN 4 , Mg 2 N 4 , and tr -BeN 4 with armchair chains, and layered GaN 5 have been synthesized at 45–85 GPa. Furthermore, LiN 5 , tr -BeN 4 , and Mg 2 N 4 can be quenched to ambient conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In the angle-resolved XRD pattern at 108 GPa, there was a significant overlap of Bragg peaks between the reacted/unreacted sample and gasket due to the tail of the X-ray beam spot (Figure S3). This phenomenon is expected in the synthesized new phases by high-pressure and high-temperature treatment. , So, we think the quality of Rietveld refinement between calculation and experiment is tolerable, considering the lower content of MnN 4 compared to the unreacted Mn sample. By comparing the XRD patterns with the crystal structures proposed in the previous study, we found that the new peaks at 108 GPa corresponded to a new nitride MnN 4 with P -1 symmetry.…”
mentioning
confidence: 96%
“…This phenomenon is expected in the synthesized new phases by high-pressure and high-temperature treatment. 36,42 So, we think the quality of Rietveld refinement between calculation and experiment is tolerable, considering the lower content of MnN 4 compared to the unreacted Mn sample. By comparing the XRD patterns with the crystal structures proposed in the previous study, 39−41 S1).…”
mentioning
confidence: 99%